Development and initial validation of the Japanese healthy work environment assessment tool for critical care settings. - Mio Kitayama; Takeshi Unoki; Yui Matsuda; Yujiro Matsuishi; Yusuke Kawai; Yasuo Iida; Mio Teramoto; Junko Tatsuno; Miya Hamamoto (PLoS ONE, 2022)
Aim This study aims to translate the Healthy Work Environment Assessment Tool (HWE-AT) into Japanese and evaluate its validity and reliability. Design and methods The authors followed the guidelines for scale translation, adaptation, and validation in cross-cultural healthcare research. After translation and back-translation, a series of pilot studies were conducted to assess comprehensibility. Subsequently, an expert panel established the content validity. Content validity was calculated using the content validity index (CVI). Finally, we verified the construct validity and calculated the test-retest reliability. Results The updated HWE-AT achieved sufficient comprehensibility after conducting the two pilot tests. Content validity was calculated using the scale-level CVI/average and all the items were 1.00. The content validity indices CFI and RMSEA were 0.918 and 0.082, respectively. Intraclass correlation coefficients for all dimensions ranged from 0.618 to 0.903, indicating acceptable test-retest reliability. Our findings suggest that the Japanese version of the HWE-AT has good validity and reliability.